Control over Power Efficiency of Industrial Consumers on the Basis of Modeling Power Consumption Modes - N. V. Tokochakova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Methodology for control over power efficiency of industrial consumers with complex technological structure (oil pipe-line transport is taken as an example) has been developed. This methodology is based on computing and statistical models of power consumption. Indices of subsystems affecting power consumption mode of the technological system as a whole are used as factors included in the model. A number of factors included in the model can be varied and a type of the model can be transformed due to a power-saving problem which is to be solved: execution of power investigation; forecasting and normalization of electric-power consumption, evaluation of target-oriented power-saving index.